Women’s attitude towards mass media advertisement - Parajuli, Pradip (Patan Pragya, 2019)
Advertising and society both are inter-related and affect each other in many ways. Sometimes the content of advertisements is guided by society and sometimes advertisements have dominance over society. Even though an advertisement is not meant to be a moral guide, it is also true that it has certain responsibilities towards the society simply because it reaches millions of homes and influences people, directly or indirectly. The mass media are essential not only in promotion and propagation of innovative ideas but also in transformation of the society. Advertisement affects and changes the behaviour, thinking, perception and ideas of people often. As an effective audio-visual media, advertising has tremendous impact on rural Nepalese society where majority of population is illiterate. Advertisements have numerous social, cultural and economic impacts upon the viewers. Advertising is a very effective tool of communication to sensitize the people in a developing country like Nepal. It has the responsibility to play an important role in the empowerment of the women particularly regarding their rights, privileges and other facilities. In this paper attempt has been done to understand the women's attitude towards mass media advertisement particularly comprehensive, useful, influence and change in behaviour.